Influence of drought stress and mycorrhizal (Funneliformis mosseae) symbiosis on growth parameters, chlorophyll fluorescence, antioxidant activity, and essential oil composition of summer savory (Satureja hortensis L.) plants - Rasouli, Farzad; Amini, Trifa; Skrovankova, Sona; Asadi, Mohammad; Hassanpouraghdam, Mohammad Bagher; Ercisli, Sezai; Buckova, Martina; Mrazkova, Martina; Mlcek, Jiri (Frontiers in Plant Science, 2023)
Introduction: Drought stress unfavorably influences the growth and physiological traits of plants in the arid and semi-arid regions of the world. The aim of this study was to determine the effects of arbuscular mycorrhiza fungi (AMF; Funneliformis mosseae) inoculation on the physiological and biochemical responses of summer savory (Satureja hortensis L.) under different irrigation regimes. Methods: The first factor was different irrigation regimes, including no drought stress (100% filed capacity; FC), moderate drought stress (60% FC), and severe drought stress (30% FC); the second factor included the plants without AMF (AMF0) and with AMF inoculation (AMF1). Results: The results showed that better values, higher plant height, shoot mass (fresh and dry weight), relative water content (RWC), membrane stability index (MSI), photosynthesis pigments, Fv, Fm, Fv/Fm, and total soluble proteins were obtained in the plants inoculated with AMF. The highest values were obtained for plants with no drought stress, then the plants subjected to AMF1 under 60% FC, and the lowest ones for plants under 30% FC without AMF inoculation. Thus, these properties are reduced under moderate and severe drought stress. At the same time, the utmost activity of superoxide dismutase (SOD), ascorbate peroxidase (APX), guaiacol peroxidase (GPX), and the highest malondialdehyde (MDA), H2O2, proline, and antioxidant activity (TAA) were achieved for 30% FC + AMF0. It was also finded that AMF inoculation improved essential oil (EO) composition, also as EO obtained from plants under drought stress. Carvacrol (50.84-60.03%) was the dominant component in EO; γ-terpinene (19.03-27.33%), p-cymene, α-terpinene and myrcene, were recognized as other important components in EO. The higher carvacrol and γ-terpinene contents were obtained from summer savory plants with AMF inoculation and the lowest for plants without AMF and under 30% FC. Conclusion: According to the present findings, using AMF inoculation could be a sustainable and eco-friendly approach to improve physiological and biochemical characteristics and the essential oil quality of summer savory plants under water shortage conditions.